Ketimpangan Sosial dan Distorsi Komunikasi dalam Novel Laskar Pelangi: Analisis Hermeneutika Kritis Jurgen Habermas - Helleri Sitinjak; Elka Anakotta; Eurene Lefta (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the novel Laskar Pelangi by Andrea Hirata using a critical hermeneutic approach developed by Jürgen Habermas. The focus of this research is to uncover the critical meaning contained in the novel as a reflection of social reality, especially in the field of education. The method used is descriptive qualitative research with data collection techniques through literature studies and text analysis in the form of excerpts in novels. The results of the study show that the novel Laskar Pelangi not only presents an inspiring story, but also contains criticism of the education system in Indonesia which is still colored by inequality and injustice. In the aspect of communicative action, it was found that there was a dialogical interaction between teachers and students as well as the value of solidarity and strong struggle. However, in the aspect of communication distortion, there is injustice in access to education and a lack of space for poor groups to voice their interests. In addition, the analysis also reveals the existence of ideology and domination, especially economic dominance over education and social systems that oppress the lower groups. On the other hand, the emancipatory interest in this novel is reflected through education as a tool of liberation and the struggle of its characters in fighting against limitations. Thus, this study concludes that the novel Laskar Pelangi has an important role as a social criticism medium that is able to build readers' critical awareness of the reality of education and social inequality that occurs in society.